Penulisan Sejarah Desa: Sebuah Model Pembelajaran untuk Tugas Akhir Mahasiswa - Mochammad Nginwanun Likullil Mahamid; Dina Ayu Ardhana; Ilham Nur Rochmad; Queen Tamalla Hasan; Hanip Hidayatulloh (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Writing a final assignment or thesis is a requirement for graduation from an undergraduate (S1) program, enabling students to develop skills in exploring ideas, identifying problems, analyzing data, and presenting findings in an academic format. Emphasizing novelty is crucial to producing high-quality theses that contribute to their field of study. However, recent final assignments by students of the Islamic Civilization History Program at UIN Sunan Ampel Surabaya have largely focused on topics such as mosques, Islamic boarding schools, traditions, and religious figures, while other potential topics, like Village History, remain underexplored despite their capacity to achieve higher academic value. This aligns with the Ministry of Home Affairs Regulation (Permendagri) No. 50 of 2021, which supports the "Cultural Advancement" program. To address this issue, this study employs a descriptive method supported by interviews from direct observations at institutions and written sources from Google Scholar and personal libraries. The activities include providing intensive mentoring to students, incorporating village history into relevant courses, and developing new supporting materials such as a village history writing module, village history podcast videos, and a Semester Learning Plan (RPS) for Village History. The implications of this research is to strengthen local wisdom, increase student interest, and strengthen the historical profile of the village.